تقييم فعالية المعالجة الوظيفية لكسور لقمة الفك السفلي دراسة متابعة طويلة الأجل - خليل, عبد الكريم; خليل, علي (Latakia University Journal -Medical Sciences Series, 2016)
تعتبر كسور اللقم الفكية السفلية شائعة الحدوث مع الرضوح الوجهية، وتمثّل معالجتها نقطة خلاف كبيرة في طب الرضوح الوجهية الفكية. المعالجات الوظيفية والجراحية هي وسيلة التدبير الرئيسية لمثل هذه الكسور. هدفت هذه الدراسة إلى تقييم نتائج المعالجة الوظيفية لكسور لقم الفك السفلي لدى المرضى الذين تلقوا هذا النوع من المعالجة. تم استدعاء 86 مريض تراوحت أعمارهم بين 6-66 سنة وممن خضعوا سابقاً لمعالجة محافظة لكسور اللقم الفكية السفلية لإجراء فحص المتابعة، مع فترة متابعة بعد المعالجة متوسطها 10,4 سنة. تم تقييم وظيفة الفك السفلي باستخدام استبيان خلل الوظيفة للفك السفلي، أما شكاوى المرضى فتم تقييمها من خلال الفحص الطبي. حيث تم تقسيم المرضى إلى 3 مجموعات عمرية مختلفة . أظهرت نتائج قيم مشعر الخلل الوظيفي تزايدا ملحوظاً مع التقدم في العمر الذي وقعت فيه الإصابة. لوحظت، وبشكل متكرر، الشذوذات الشعاعية مثل قصر في ارتفاع الرأد، انحراف الخط الناصف للفك السفلي والشكل غير المنتظم للقم الفكية؛ لكنها لم تكن مترابطة مع شدة الخلل الوظيفي. المنبئات لخلل وظيفة الفك السفلي بعد المعالجة الوظيفية لكسور اللقم الفكية السفلية كانت: الانحراف الجسيم، التحدد في فتحة الفم، جنس الإناث والتقدم في العمر. تدعم نتائج هذه الدراسة الآراء التي تعتبر المعالجة الوظيفية كافية عند المرضى الأطفال، بينما في مجموعات الأعمار المتقدمة فإن المعالجة المحافظة غير كافية. Fractures of the mandibular condyles are frequent in facial traumas and their treatment represents a highly controversial issue in maxillofacial traumatology, functional and surgical treatments being the two principal management modalities for such fractures. The aim of this study is to evaluate the results of functional treatment of mandibular condylar fractures in patients which received this type of treatment. Eighty-six patients between 6 and 66 years old who were previously treated fuctionally for a fracture of the mandible condyle were recalled for follow –up examination with a mean postoperative observation time of 10.4 years. Mandibular function was assessed using the mandibular function impairment questionnaire and patient’s complaints were assessed during physical examination. The results showed a significant increase of dysfunction index values with increasing age at the time of trauma. Radiologic abnormalities such as reduced ramus height, deviation of the mandibular midline, and irregular shape of the condyle were observed and seen frequently, but they were not correlated with the severity of dysfunction. Predictors of mandibular function impairment after closed treatment of fractures of the mandibular condyle were: great deviation, reduced mouth opening, women gender, and increased age. The results of this study support the opinion that functional treatment is sufficient in pediatric patients, whereas in older age groups the results of conservative treatment are less sufficient.